2006
DOI: 10.1182/blood-2006-11-010389
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of T-cell functions by human granulocyte arginase

Abstract: Chronic inflammation is accompanied by impaired T-cell immunity. In the mouse, myeloid cell-associated arginase accounts for the suppression of immune reactivity in various models of tumor growth and chronic infections. Here we show that arginase I is liberated from human granulocytes, and very high activities accumulate extracellularly during purulent inflammatory reactions. Human granulocyte arginase induces a profound suppression of T-cell proliferation and cytokine synthesis. This T-cell phenotype is due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
367
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(395 citation statements)
references
References 37 publications
22
367
2
4
Order By: Relevance
“…diminished production of IFN-g and downstream effectors, is most relevant for the failure of IL-18 KO mice to control mycobacteria. Arginase-1 has also been detected in PMN [28,29]. Thus, the vast number of PMN in IL-18 KO lungs represents an additional or alternative source for arginase-1.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…diminished production of IFN-g and downstream effectors, is most relevant for the failure of IL-18 KO mice to control mycobacteria. Arginase-1 has also been detected in PMN [28,29]. Thus, the vast number of PMN in IL-18 KO lungs represents an additional or alternative source for arginase-1.…”
Section: Discussionmentioning
confidence: 97%
“…Both IL-18 and MyD88 KO lungs show diminished expression of TNF-b, which is directly involved in organization of granulomas in mycobacterial infection [13]. Furthermore, up-regulation of arginase-1 could result in a negative nitrogen balance within the lung tissue by depletion of arginine, which is an important micronutrient for T-cell proliferation and cytokine synthesis [29,35]. The strong influx of metabolically active cells may further deplete micronutrient sources [36].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this correlation of NLR with poor prognosis is largely unknown. However, in this respect it has been reported that normal neutrophils are able to suppress T‐cell function, while activated neutrophils have increased levels of arginase 1, which also cause T‐cell suppression 20. In addition to contributing to T‐cell immune suppression, neutrophils may also exhibit tumor‐promoting capabilities, like the induction of angiogenesis and enhancement of tumor spread by enhancing the expression of matrix metalloproteinase 9 10…”
Section: Discussionmentioning
confidence: 99%
“…Although the local consumption of multiple EAAs would seem to represent a redundant and therefore functionally robust system, each individual enzyme probably has additional specialized immunomodulatory properties. For example, IDO appears to be primarily expressed within APCs, requiring the appropriate tryptophan transporters to achieve extracellular depletion of tryptophan (24), whereas arginase can be secreted by neutrophils to deplete extracellular arginine (25). There are also specific functions for some of the products of amino acid consumption, such as kynurenines generated from tryptophan by IDO and NO generated by iNOS from arginine.…”
Section: Discussionmentioning
confidence: 99%